2019
DOI: 10.5530/pj.2019.11.76
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic, Antibacterial and Antioxidant Activities of Different Extracts from Brucea javanica (L.) Merr Seeds

Abstract: Introduction: The seeds of B. javanica are known as herbal material for anticancer, antimalaria and antiamoeba. Limited report is available on their antidiabetic and antibacterial properties. Methods: Methanol (ME) and Ethyl acetate extracts (EAE) were studied for their inhibition activities on α-glucosidase in vitro, including combination of ME with acarbose and inhibition mechanism. Antibacterial activity was tested by well diffusion and microdilution methods. The extracts were evaluated for their in vitro a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…INPA and EEPA were determined for their phenolic contents based on the Folin-Ciocalteu method as reported previously. 11 In brief, sample (0.5 mL) was mixed with Folin-Ciocalteu reagent (10% v/v, 2.5 mL), and left to stand for 10 mins. The mixture was then added with Na 2 CO 3 (75 g/L, 2.5 mL) and incubated at room temperature for 2 h. The absorbance was measured at 765 nm.…”
Section: Determination Of Total Phenolic Content (Tpc)mentioning
confidence: 99%
See 1 more Smart Citation
“…INPA and EEPA were determined for their phenolic contents based on the Folin-Ciocalteu method as reported previously. 11 In brief, sample (0.5 mL) was mixed with Folin-Ciocalteu reagent (10% v/v, 2.5 mL), and left to stand for 10 mins. The mixture was then added with Na 2 CO 3 (75 g/L, 2.5 mL) and incubated at room temperature for 2 h. The absorbance was measured at 765 nm.…”
Section: Determination Of Total Phenolic Content (Tpc)mentioning
confidence: 99%
“…α-Glucosidase inhibition activity of INPA and EEPA was determined based on a reported method. 11 In this method, p-nitrophenyl glucopyranoside (pNPG) was used as a substrate and acarbose was used as a reference inhibitor. Sample of different concentrations (50 µL) was mixed with α-glucosidase (0.5 U/mL, 50 µL) and phosphate buffer (50 mM pH 6.8, 50 µL).…”
Section: Determination Of α-Glucosidase Inhibition Activitymentioning
confidence: 99%
“…Brucea javanica has been shown to have activities such as antitumor 20 , antidiabetic 21 , antihyperlipidemic 22 , antioxidant, and antibacterial 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Plants remain the primary source for the discovery and development of antidiabetic and antiobesity agents 10,11 . Studies related to pure compounds of plant origin have shown promising responses against diabetes and obesity [12][13][14] .…”
Section: Introductionmentioning
confidence: 99%